Determination of the optimal time for the heat treatment time of local canned river and marine fish products in Basra Governorate, knowledge of microbial analysis and sensory evaluation - Mansour, H. T; Majeed, K. R; Al-Temimi, W. K (Zien Journals, 2023)
A microbial and sensory study was conducted to evaluate the final quality of the canned product of river Mullte fish, Mackrele marine fish, and Talange Queen marine fish. The fish were brought from the official areas designated for selling fish in Basra Governorate in fresh condition and placed in an ICE BOX with the addition of crushed ice at a temperature of 4±1. The microbial composition was studied before and after processing and during storage periods (0, 15, 30, 45 and 60) days. At the end of the storage period, a sensory evaluation of canned fish was conducted. By conducting tests, it was found that Mullte fish, Mackrele fish, and Talange Queen marine fish are suitable for a process in the fish canning industry because it retains the largest amount of nutritional value. The D value was (0.88, 1.64, and 1.67) minutes for canned fish, respectively, that were canned with 2% saline solution and during storage periods of (0, 15, 30, 45, and 60) days. The F0 values were (3.75, 6.96 and 7) minutes, respectively. The highest sensory evaluation was for Talange Queen, Mackrele and Mullte fish. The product shall be free at each storage period of any microbial growth.
Keywords: D value; F value; microbial analysis; sensory evaluation